Ethical issues in paleopathological and anthropological research experiences - Licata, Marta; Monza, Francesca (Acta Biomedica Atenei Parmensis, 2017)
Background and aim: In recent years, archaeologists and anthropologists involved in the study of human remains have had to take into consideration ethical issues, which have come to the fore. The aim of this study is to illustrate the ethical and religious issues involved in relation to the positions of researchers. Method: Ethical issues involve the different study phases of human remains: archaeological excavation, anthropological analysis and, finally, museum display. Results: Osteoarchaeological remains may find a place in museums. However, in recent years, even the display of human remains museum has had to face new important ethical issue involving previously ignored or neglected aspect. The adoption of Native American Grave Protection Act in 1990 in the United States and the Human Tissue Act in 2004 in England, has created new scenarios relating to the storage of human remains in museum. Conclusion: All this caused a series of changes in the study of human remains, but many issues remain open to debate.